Seasonal Activities of Larval Emergence in Lac Insect Kerria lacca (kerr) (Homoptera-Tachardiidae) - Kulkarni, S. M. (Indian Forester, 1967)
There are four seasonal lac crops during the year of which Baisakhi and Katki are known as Rangeeni crops and Aghani, Jethwi are being Kusumi crops. Number of larvae emerge more in Rangeeni crops than the Kusumi crops July-August being the more favourable time for more larvae to emerge in Baisakhi and ]ethwi crops than the Katki in October-November and Aghani in February-March. Period of larval emergence is more in Baisakhi and Jethwi than Katki and Aghani. Maximum number of larvae emerge on a single day from a single mother cell in all the seasons falls between 2nd and 5th day, peak period being the 3rd day. From the date of emergence, the viability of larval emergence continues in all the cells till 4th day and then decrease. Gradually from 5th day till emergence subside. Maximum number of larvae emerge from a single mother cell on a single day is 176.84 in Baisakhi, 149.78 in Katki crops whereas 8128 and 89.64 in Aghani and fethwi crops respectively. Average larval emergence period in Rangeeni crops varies from 6.36 to 8.72 days whereas in Kusumi crops it ranges from 5.68 to 7.11 days .Average number of larvae emerge from a single Rangeeni mother cell varies from 305.86 to 779.92 whereas in Kusumi crops it ranges from 246.42 10 439.2l.